Can sociality buffer the impacts of climate change on a cooperatively-breeding bird, the southern pied babbler Turdoides bicolor? - Bourne, Amanda R (University of Cape Town, 2020)
Increasingly harsh and unpredictable climate regimes are affecting animal populations everywhere and understanding how species respond to current environmental variability is important for predicting vulnerability to climate change over longer timescales. Species living in characteristically harsh and unpredictable arid and semi-arid ecosystems are useful models for studying impacts of climate variability and change because these ecosystems are experiencing rapid increases in both average and maximum temperatures, as well as increased interannual rainfall variation, as a result of anthropogenic climate change. That animals living in highly variable environments are disproportionately more likely to engage in cooperative breeding implies that this strategy may buffer individuals against the negative effects of adverse climate conditions. An aspect of species' vulnerability to climate change that remains relatively unexplored is whether responses to environmental stressors might therefore be mitigated by sociality, particularly in those species in which group members are highly cooperative. In this thesis, I use behaviour, morphology, and physiology data that I collected over three consecutive austral summer field seasons (2016-2019) and A. Prof. Amanda Ridley's 15-year life history dataset (2003-2019, to which I contributed the last three years of data) for a cooperatively-breeding bird, the southern pied babbler Turdoides bicolor. I investigate the impacts of temperature, rainfall, and group size on interannual survival, behaviour, physiology, growth, and reproduction in southern pied babblers, taking a multidisciplinary approach combining behavioural ecology, life history, and ecophysiology. In order to avoid disturbance to the study population, I validated and implemented a non-invasive method for collecting physiological measurements (daily energy expenditure and water turnover). I also tested for the influence of interactions between weather and group size variables because the presence of significant interactions would provide evidence in support of a moderating effect of sociality. I found that exposure to high temperatures significantly constrained successful breeding and the interannual survival of both breeding adults and juvenile birds, and explored the mechanisms behind these observed relationships: adjustments in parental care behaviour, body mass loss, reduced nestling growth rates, and the physiological costs of care at high temperatures. Higher rainfall and larger groups sizes were generally associated with higher reproductive success and survival, but I found no evidence for an interaction between weather variables and group size: individuals across all group sizes experienced similar effects of conditions. I therefore conclude that 1) pied babblers will increasingly face challenges for population recovery and persistence in the near future as survival and reproduction are increasingly compromised by ever higher temperatures, and 2) a life history strategy that relies on the presence of helpers for successful breeding is unlikely to buffer individual group members against climatic variability and climate change in this cooperatively breeding species.